2013
DOI: 10.3389/fonc.2013.00057
|View full text |Cite
|
Sign up to set email alerts
|

A decade in banking Ewing sarcoma: a report from the Children’s Oncology Group

Abstract: Outcomes for patients with metastatic and recurrent Ewing sarcoma remain poor and a better understanding of the biology of this malignancy is critical to the development of prognostic biomarkers and novel therapies. Therefore, the Children’s Oncology Group (COG) has created tissue banking protocols designed to collect high quality, clinically annotated, tumor specimens that can be distributed to researchers to perform basic science and correlative investigation. Data from the COG Ewing sarcoma tissue banking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Although some advances have been developed in the treatment strategies for ES, very little improvement was achieved in the 5-year survival rates. The disease-free survival of patients with over metastases is < 30%, and this rate has not experienced any improvements over the last 30 years (Borinstein et al, 2013). Thus, a better understanding of the pathological mechanisms about this malignancy is critical to the development of prognostic biomarkers and novel therapies.…”
mentioning
confidence: 99%
“…Although some advances have been developed in the treatment strategies for ES, very little improvement was achieved in the 5-year survival rates. The disease-free survival of patients with over metastases is < 30%, and this rate has not experienced any improvements over the last 30 years (Borinstein et al, 2013). Thus, a better understanding of the pathological mechanisms about this malignancy is critical to the development of prognostic biomarkers and novel therapies.…”
mentioning
confidence: 99%
“…All tumor samples were from patients with a pathologically confirmed diagnosis of primary Ewing sarcoma who were enrolled in a large multicenter COG protocol, AEWS0031 [21],[23]. AEWS0031 was opened for enrollment on May 2001 and closed in August 2005.…”
Section: Resultsmentioning
confidence: 99%
“…This is a particularly attractive aspect of this methodology as reliable acquisition of baseline tumor tissue has proven difficult in North American cooperative group ES banking studies. 34 In this study, we demonstrated the ability to identify fusion breakpoint sequences in the majority of plasma cfDNA samples, along with potentially prognostic alterations in TP53 and STAG2. Although NGS was successful at identifying fusions in the majority of baseline cfDNA samples, there were several examples in which ddPCR was able to identify a very low level of fusion positivity that was not identified by NGS.…”
Section: Discussionmentioning
confidence: 75%